Correction: An analysis of the distribution of bone and soft tissue sarcoma diagnoses and their disparities in Southwest Germany: a multicenter approach : correction - Calukovic, Branko; Benzler, Katrin; Carter, Mary E.; Daigeler, Adrien; Thiel, Johannes T.; Jakob, Jens; Kasper, Bernd; Egerer, Gerlinde; Apostolidis, Leonidas; Braig, David; Hettmer, Simone; Blattmann, Claudia; et al. (Frontiers in oncology, 2025)
Correction on: Calukovic B, Benzler K, Carter ME, Daigeler A, Thiel JT, Jakob J, Kasper B, Egerer G, Apostolidis L, Braig D, Hettmer S, Blattmann C, Knott M, Zender L and Deinzer CKW (2025) An analysis of the distribution of bone and soft tissue sarcoma diagnoses and their disparities in Southwest Germany: a multicenter approach. Front. Oncol. 15:1592004. doi: 10.3389/fonc.2025.1592004.Wrong content There was a mistake in figure 3 as published. By mistake, all five maps in figure 3 showed only the sarcoma primary cases of the Sarcoma Center Stuttgart. The corrected figure 3 appears below. The original version of this article has been updated.
Gesehen am 29.01.2026